The social effects of economic thinking / William Van Lear. - Van Lear, William (Palgrave Pivot, 2014)
The theories and hypotheses driving economic modeling and policy have real-world, tangible effects on the lives of those implicated. As such, ideologies play a particularly challenging role in economic policymaking, as the decisions made by governing bodies have the potential to alter the lives of many. In this engaging work, Van Lear paints a vivid picture of the social implications of economic thought, creating a careful narrative which stresses the importance behind turning ideas into action within the economic world. This book aims to explain how social outcomes result from the influence of economic ideas which are themselves strongly impacted by the distribution of power in society. Often ideas and policies are about promoting certain vested interests. The important role of vested interests is covered-over in the political arena by focus on competing ideas that usually ignore economic interests and efforts to control social norms and conditions. In the context of American history, the manuscript examines the policies and programs of contending interests, and emphasizes the importance of current socio-economic issues emanating from the modern trend of the economy towards quasi-economic stagnation.